Kerkelijke Eigendom : Memahami Hak Milik Gereja Di Indonesia Era Kolonial - Juwono, Harto (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
This research aims to elucidate the history of land ownership by Christian Church institutions in the Dutch East Indies colony. In addition to providing a descriptive account of its development, this article endeavors to delve into various documentary sources concerning ownership, particularly the legal status associated with the Christian Church as an institution within the colonial legal framework. Through an examination of its legal standing, this research seeks to discern the nature of the Church's land ownership. Given the historical nature of this study, the historical method is employed to guide the research towards a comprehensive reconstruction. This method comprises five phases: document exploration (heuristic), critical analysis, exceptions, interpretation, and reconstruction. Emphasis is placed on authentic documents to ensure the accuracy and objectivity of the information presented in this reconstruction. In conclusion, this report elucidates the legal status of the Christian Church under the colonial legal system and its implications for material ownership by the Church based on its legal standing. Thus, shedding light on the origins of asset ownership status held by the Christian Church in present-day Indonesia.